Evaluation of antidiabetic properties of Moringa oleifera Lam. leaves using In vitro model - Mohamad Mokhtar, Muhammad Hanaffi (2015)
Diabetes mellitus is a chronic condition affecting million of people worldwide including Malaysia. 347 million of people worldwide suffering diabetes and National Health and Morbidity Survey in 2011 showed that 20.8 % of Malaysian population suffering diabetes. Even though plenty of antidiabetic drug are available, it is still remain the major worldwide health problems, which possibly due to the current drug adverse side effect and its poor clinical efficacy. Continuous efforts are needed in searching for new, safe and efficacious antidiabetic drug. Moringa oleifera is one of the common medicinal plant uses in folk medicine. Traditionally, it has been claimed to possess antidiabetic property. The study was carried out to authenticate the claimed antidiabetic property and its possible mode of actions. In this study, antioxidant capacity and antidiabetic evaluations on hot aqueous M. oleifera leaves extract using in vitro model were done. Phytochemical study on M. oleifera indicated the presence of polyphenols, with total phenolics content was found to be 3550 ± 100 mg gallic acid equivalent per 100 g dry matter basis. It was shown from β-carotene bleaching assay that M. oleifera preventing degradation of β-carotene by the peroxyl radicals and exhibited 36% antioxidant capacity, whereas 2,2-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay exhibited that IC50 for hot aqueous M. oleifera was 0.32 mg/ml, suggesting that the extract potentially possesses free radical scavenging ability. Toxicity evaluation by cell viability assay showed that M. oleifera did not cytotoxic to BRIN-BD11, 3T3F442A adipocytes, L6 myotubes and Chang liver cells. Studies on antidiabetic mechanism had shown that hot aqueous M. oleifera stimulated insulin secretion from pancreatic β-cells significantly (p< 0.01). It had been found that maximal insulin secretion ability of M. oleifera was 4.66 fold higher than glibenclamide. M. oleifera enhanced basal and insulin-mediated glucose uptake into adipocytes, muscles and liver cells. Insulin mimetic property was observed in 3T3F442A adipocytes cells whereas insulin sensitizing property and synergistic effect with insulin property were observed in all cells tested. In vitro α-glucosidase inhibition activity had shown that hot aqueous M. oleifera significantly inhibited rat intestine sucrase activity with IC50 value of 977.24 μg/ml and exhibited competitive-type inhibition mechanism with Vmax value of 0.283 ± 0.003 mM/mg protein/min. This study showed that M. oleifera possesses antidiabetic properties as claimed by the folk medicine practitioners. Coupled with its antioxidant properties, it is suggested that the plant has a potential to be developed as a new plant-derived oral antidiabetic agent.